The Idea of Fusing Duality into Unity as a Bridge between Engineering and Buddhist Thought: Annotated Report of the Author’s Interview with Dr. MORI Masahiro, a Well-Known Japanese Scholar of Robotics, in the Television Program - MARUI, Hiroshi (SEISAN KENKYU, 2022)
The present paper is an annotated report of the author’s interview with Dr. MORI Masahiro, a renounced pioneer of robotics in Japan, in the NHK E-television program (broadcast on June 30, 2019) entitled “The Idea of Fusing Duality into Unity as a Bridge between Engineering and Buddhist Thought.” In some sense, it may be said that the idea of fusing a dichotomy into unity constitutes the core principle of Buddhist thought. According to Dr. Mori, this principle is also applied in developing and utilizing various technological devices. How to harmonize accelerating with braking is a central concern in the task of making a car and driving it as well. Moreover, he emphasizes that there is another aspect of the same principle which plays an important role in the Buddhist notion of good and bad. That is, the dichotomy of good and bad should be traced back to the common ground that is inexpressible in either way. In other word, the bad may be converted to the good by means of turning it back to that inexpressible, but the mental control is regarded as a requirement for this end. Since any technological product may serve for good and bad, how to harmonize the technological development with the ethical dimension should be one of the inevitable issues for the future of human beings and even of the earth. In this paper the author presents several aspects of Dr. Mori’s philosophy of “monozukuri wa hitozukuri” (To develop things is to develop mind) because the author thinks that his philosophy will cast a light of hope for the solution of that issue.